A novel therapeutic strategy of methicillin-resistant Staphylococcus aureus - Ying Wang; Mengyan Xu; Hanne Ingmer (Engineering Microbiology)
Staphylococcus aureus is a major public health threat, largely due to its remarkable capacity to develop antimicrobial resistance. Zhang et al. recently demonstrated a highly innovative approach to eradicate chronic methicillin-resistant S. aureus infections by inducing bacterial calcification with antibody-polysialic acid conjugates targeting wall teichoic acids, while simultaneously modulating host immune responses via enhanced calprotectin expression and macrophage activation. Despite limitations, this strategy represents a promising and unconventional therapy to combat resistant S. aureus infections.